Produtividade em colônias de Polistes (Ap hanilopterus) vers icolor Olivier, 1791 (Hymenoptera: Vespidae, Polis tinae) - Gobbi, Nivar; Govone, Jose Silvio; Outeiro Pinto, Nozor Paulo; Prezoto, Fabio (My University, 2009)
From August 2000 to December 2003, 185 colonies of Polistes versicolor were observed at the Bioterio of the Instituto de Biociencias, UNESP, Campus de Rio Claro, SP. In 144 colonies (77,84%) didn't emerge wasps, and of others 41 (22,16%), in 16 it was not possible to obtain the number of meconia, because they were attacked in several degrees of injury by natural enemies such as, ants, birds and parasitic wasps. The colonies productivity was measured through the meconia count in the cells of 25 colonies, which ranged from 1 to 6 meconia by cell.
Colonies productivity of Polistes (Aphanilopterus) versicolor Olivier, 1791 (Hymenoptera: Vespidae, Polistinae).